Long-Term Follow-Up Of The Remaining Kidney Function In Patients After Nephrectomy (Eurasian Medical Research Periodical, 2025)
This article analyzes the long-term dynamics of the remaining kidney function in patients after nephrectomy. The compensatory capacity, time-related changes in functional parameters, and clinical outcomes were studied. Based on the follow-up results, conclusions were drawn regarding the risk of renal failure, arterial hypertension, and metabolic disorders